Self-medication in academic course graduate of health in a private university of the state of Rio Grande do Sul - Thricy Dhamer; Ana Paula Dal-Molin; Ana Helfer; Lia Gonçalves Possuelo; Marcelo Carneiro; Carla Kauffmann; Andréia Rosane Moura Vallim (Universidade de Santa Cruz do Sul, 2012)
Rationale and Objectives: The World Health Organization defi nes self-medication as the selection and use of medicines by individuals to treat their illnesses or symptoms. It is considered a public health problem that deserves special attention, since it presents risks, because of adverse drug reactions, bringing serious consequences and may lead to the death. To determine the prevalence and characteristics of self-medication realized by undergraduate students enrolled in health courses in a community college, as well the symptoms that led to this practice. Methods: This study was an observational and quantitative research, where it was used structured and pre-coded questionnaires to obtains the data, among students enrolled at 5th and 6th semesters of Biology, Physical Education, Nursing, Pharmacy, Physiotherapy, Medicine, Nutrition, Dentistry and Psychology at the University of Santa Cruz do Sul. Results: 342 students were evaluated, 74% female, aged between 18 and 50, which was the most prevalent age group of 21-30 years, which were 71.4% of students. The prevalence of medicines used among those surveyed was 68.7% last month, with an average of 2 medications per student. The medications were distributed by medical prescription in 282 cases (59.1%), under self-medication in 139 cases (29.1%), oriented by a pharmaceutical in 25 cases (5.2%) and no response in 31 cases (6.6%). The classes of drugs most used were analgesics/antipyretics (48.2%), NSAIDs (14.2%) and antacids (9.9%). The main purpose of motivating self medication were headache (14.4%), digestive disorders (13.2%), contraception (7.2%) and general pain (6.0%). Conclusion: Self medication is a common practice among students in the health area, where about a third reported conduct such practice. KEYWORDS Self-medication. Student Health Occupations. Drugs.